Microwave ferrite material as well as preparation method and application thereof

By doping barium ferrite with Cu and co-substituted metals to co-substitute Fe sites, and adjusting the doping amount to reduce the magnetocrystalline anisotropy field, the natural resonance frequency of the ferrite material is continuously variable in the X-band. Adjustment solves the problem of insufficient performance of existing materials in high-frequency microwave communications.

CN119350014APending Publication Date: 2025-01-24GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411532423.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The natural resonance frequency of existing ferrite materials cannot be continuously adjustable in the X-band (8.5 to 14.6GHz), and the saturation magnetization and coercivity are insufficient, which cannot meet the needs of high-frequency microwave communication.

Method used

By mixing CU and coexisting metal (such as 铪, 锆 or titanium) in the iron oxygen body, replace the FE bits, adjust the doping amount to reduce the opposite sex field of the magnetic crystal, and achieve the continuous adjustment of the natural resonance frequency. And improve the saturated magnetization strength.

Benefits of technology

The natural resonance frequency of microwave iron oxygen materials is continuously adjusted in the X -band, which improves the saturated magnetization strength and electromagnetic properties, meets the needs of high -frequency microwave communication. At the same time, the preparation method is simple and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350014A_ABST
    Figure CN119350014A_ABST
Patent Text Reader

Abstract

The invention relates to a microwave ferrite material and a preparation method and application thereof, the chemical formula of the microwave ferrite material is BaFe (12-2x) (MeCu) xO19, Me is a co-substituted metal and comprises any one or a combination of at least two of hafnium, zirconium or titanium, and x is greater than or equal to 0.25 and less than or equal to 1.0; according to the invention, on the basis of barium ferrite BaFe12O19, a specific amount of transition metal elements with different valences are doped to jointly replace the Fe site of the ferrite, so that the magnetocrystalline anisotropy field of the obtained material is reduced, the coercive force and saturation magnetization are effectively adjusted by regulating and controlling the doping amount, the continuous adjustment of the natural resonance frequency in the range of 8.5-14.6 GHz is realized, and the preparation method is simple and easy to implement. The requirement of developing microwave communication to high frequency is met; and the preparation method is simple, low in cost and easy for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic materials and preparation thereof, and in particular to a microwave ferrite material and a preparation method and application thereof; in particular to a microwave ferrite material with a natural resonance frequency continuously adjustable in an X-band and a preparation method and application thereof. Background Art

[0002] At present, with the continuous development and application of high-performance electronic information materials, their role in the development of high-precision electronic and microwave devices has become more and more significant, especially the development of magnetoelectric multifunctional materials with good high-frequency magnetic properties and dielectric properties has become the focus of current research. The magnetic properties and dielectric properties of materials are two basic physical properties for the preparation of passive devices. Materials with high magnetic properties and dielectric properties can be widely used in the production of various devices. However, in the context of the rapid development of microwave devices and communication technology, the research and development of ferrite magnetoelectric materials has lagged behind significantly, and the means of regulating the magnetic properties, dielectric properties and loss characteristics of ferrites are relatively single, especially the application is mainly concentrated in the lower frequency bands. As the frequency of microwave communication continues to develop towards high frequencies, improving the application frequency and high-frequency magnetoelectric properties of ferrites has become an important research direction.

[0003] Due to its unique crystal structure, hexagonal ferrite exhibits high magnetocrystalline anisotropy and magnetocrystalline anisotropy field, and the corresponding cutoff frequency of hexagonal ferrite is also high. Snoek's law states that the initial permeability μ of a magnetic material under the action of an alternating magnetic field is i With the cut-off frequency f r The product of is close to a constant. This law is a key law of the basic properties of magnetic materials. In the absence of an external magnetic field, the magnetic moment inside the ferrite is always oriented in the direction of lowest energy determined by the anisotropy field. By regulating the doping of different ions at specific crystal positions to affect its magnetocrystalline anisotropy, the coercive force and cutoff frequency of M-type hexagonal ferrite can be reduced. The method of increasing the initial magnetic permeability of ferrite through Snoek's law has great development potential.

[0004] CN109761595A discloses a ferrite used in an isolator and a circulator for 5G communication and a preparation method thereof. The ferrite material has a 4πMs of 1650Gs and a dielectric constant of ε r 14-14.5, Curie temperature 190-200℃, dielectric loss 1.50×10 -4 -1.81×10 -4 , high performance and low loss; however, its natural resonance frequency is only 3.3-3.6 GHz, and the continuous adjustability of the natural resonance frequency is not achieved, which cannot meet the needs of use at higher frequencies.

[0005] CN114628104A discloses a preparation method of a planar anisotropic soft magnetic material, and its composition includes Sm 1- x RE x (Fe 0.8 X 0.2 ) 12-y M y , where Sm is samarium, RE is zirconium, Fe is iron, X is selected from cobalt, manganese, nickel, aluminum, copper, and M is selected from titanium, vanadium, tungsten, 0 < x < 1, 0 < y < 12; similarly, it also fails to achieve continuous tunability of the natural resonance frequency in the range of 2 - 18 GHz, and there is still much room for improvement in the saturation magnetization intensity. Moreover, its preparation process is complex and the raw material cost is high.

[0006] Based on this, how to develop a new type of microwave ferrite material with continuously tunable natural resonance frequency in the X-band (8.5 - 14.6 GHz) and its preparation method, and obtain lower coercivity and higher saturation magnetization intensity has become an urgent problem to be solved in the field of magnetic materials. Summary of the Invention

[0007] To solve the above technical problems, the present invention provides a microwave ferrite material, its preparation method and application. By replacing the Fe site in the ferrite BaFe 12 O 19 with Cu and co-substituted metals, the coercivity and natural resonance frequency of the material are reduced. By regulating the doping amount, continuous tunability of the natural resonance frequency in the X-band is achieved, and the saturation magnetization intensity is increased, meeting the requirements of the development of microwave communication towards high frequencies; it can be used in the fields of wave absorption or electromagnetic shielding; and its preparation method is simple, the raw materials are widely available, and the cost is low.

[0008] To achieve this purpose, the present invention adopts the following technical solutions:

[0009] In the first aspect, the present invention provides a microwave ferrite material, and the chemical formula of the microwave ferrite material is BaFe (12-2x) (MeCu) x O 19 , where Me is a co-substituted metal, and Me includes any one or a combination of at least two of hafnium, zirconium or titanium, and 0.25 ≤ x ≤ 1.0.

[0010] Among them, Me includes any one or a combination of at least two of hafnium, zirconium or titanium. Typical but non-limiting combinations include combinations of hafnium and zirconium, zirconium and titanium, or hafnium and titanium, etc.; 0.25 ≤ x ≤ 1.0, for example, it can be 0.25, 0.45, 0.65, 0.85 or 1.0, etc.

[0011] The invention dopes barium ferrite with a specific content of a specific transition metal element with different valence states to co-replace the Fe position of the barium ferrite, and can reduce the magnetocrystalline anisotropy field of the obtained microwave ferrite material by adjusting the doping amount, effectively adjust the coercive force and the natural resonance frequency, and improve the saturation magnetization intensity; the electromagnetic properties of the obtained microwave ferrite material are comprehensively improved; if the doping amount is too small, that is, x is less than 0.25, the magnetocrystalline anisotropy of the obtained microwave ferrite material is still relatively high, and the degree of reduction of the natural resonance frequency is reduced, that is, the natural resonance frequency is still relatively high (greater than 15GHz); if the doping amount x is greater than 1.0, the dielectric properties of the material will be deteriorated.

[0012] It is worth noting that, in order to ensure charge balance, the molar ratio of copper to the co-substituted metal in the microwave ferrite material of the present invention is preferably (0.9-1.1):(0.9-1.1), for example, it can be 0.9:1, 0.9:1.1, 1:0.9, 1:1, 1:1.1, 1.1:0.9 or 1.1:1, etc.

[0013] Preferably, the natural resonance frequency of the microwave ferrite material is continuously adjustable within the range of 8.5 to 14.6 GHz, for example, it may be 8.5 GHz, 10 GHz, 12.5 GHz, 14 GHz or 14.6 GHz.

[0014] The present invention co-replaces the Fe position in the ferrite by doping a specific amount of transition metal elements of different valences, so that the natural resonance frequency of the microwave ferrite material can be continuously adjusted within 8.5-14.6 GHz, so that it can be applied to different devices according to needs, especially to meet the needs of high-frequency devices; in particular, the Hf element, because it is generally tetravalent, can cooperate with the Cu element to achieve charge balance, co-replace the Fe position, and effectively reduce the magnetocrystalline anisotropy field of the obtained microwave ferrite material, thereby effectively adjusting the saturation magnetization intensity and coercive force.

[0015] In a second aspect, the present invention provides a method for preparing the microwave ferrite material according to the first aspect, the preparation method comprising the following steps:

[0016] (1) mixing a barium source, an iron source, a copper source and a co-substituted metal source and performing a first ball milling to obtain a first ball milling slurry;

[0017] (2) pre-calcining the first ball-milled slurry in step (1) to obtain a pre-calcined material;

[0018] (3) subjecting the pre-sintered material in step (2) to a second ball milling, washing and drying in sequence to obtain a second ball milled material;

[0019] (4) The second ball mill material in step (3) is granulated, pressed and sintered in sequence to obtain the microwave ferrite material.

[0020] The preparation method of the microwave ferrite material provided by the present invention prepares the microwave ferrite material with high saturation magnetization intensity, low coercive force and adjustable natural resonance frequency through mixing raw materials, first ball milling, pre-sintering, second ball milling, granulation, pressing and sintering processes; not only does it not require complex synthesis equipment, the process is simple and the cost is low, but it also does not require the use of highly toxic chemical reagents, and can be used for large-scale industrial production.

[0021] Preferably, the barium source, iron source, copper source and co-substituted metal source in step (1) are barium carbonate, iron oxide, copper oxide and co-substituted metal oxide, respectively.

[0022] Preferably, the molar ratio of the sum of the copper oxide and the co-substituted metal oxide to the barium carbonate is (0.5-2.0):1.05, for example, it can be 0.5:1.05, 0.7:1.05, 0.9:1.05, 1.2:1.05, 1.5:1.05, 1.8:1.05 or 2.0:1.05, etc.

[0023] Preferably, the molar ratio of the sum of the copper oxide and the oxide of the co-substituted metal to the iron oxide is (0.5-2.0):(9.2-10.6), for example, it can be 0.5:9.2, 0.5:9.5, 0.5:10.0, 0.5:10.3, 0.5:10.6, 0.8:9.5, 0.8:10.2, 1.0:9.3, 1.0:10.4, 1.5:9.8, 1.5:10.6, 2.0:9.2, 2.0:10.0 or 2.0:10.6, etc.

[0024] The present invention selects a molar ratio of the sum of the copper oxide and the oxide of the co-substituted metal to the carbonate of barium (0.5-2.0):1.05, and a molar ratio of the sum of the copper oxide and the oxide of the co-substituted metal to the oxide of iron (0.5-2.0):(9.2-10.6), that is, the actual usage amount of the barium carbonate used in the preparation process is larger than the required amount calculated according to the ratio, and the usage amount of the cerium-based iron oxide used is smaller than the required amount calculated according to the ratio, that is, a "barium-rich and iron-deficient" formula. On the one hand, the influence of the volatilization of the barium element in the preparation process on the overall ratio of the obtained material is reduced, and on the other hand, the generation of divalent iron ions is reduced, the generation of impurities is reduced, and the dielectric properties of the material are enhanced.

[0025] Preferably, the mixing in step (1) further comprises adding a solvent and a grinder.

[0026] Preferably, the mass ratio of the raw materials composed of the barium source, iron source, copper source and co-substituted metal source in step (1) to the solvent and the abrasive tool is (1.5-2.5):(2.5-3.5):(3.5-4.5), for example, it can be 1.5:2.5:3.5, 1.5:3:4, 2:3:4, 2:3.2:3.8, 2.2:3:4.3 or 2.5:3.5:4.5, etc.

[0027] Preferably, the rotation speed of the first ball mill in step (1) is 800-1200 r / min, for example, it can be 800 r / min, 850 r / min, 900 r / min, 950 r / min, 1000 r / min, 1050 r / min, 1100 r / min, 1150 r / min or 1200 r / min, etc.

[0028] Preferably, the first ball milling time in step (1) is 6 to 8 hours, for example, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours.

[0029] Preferably, the pre-firing temperature in step (2) is 900-1200°C, for example, it can be 900°C, 950°C, 1000°C, 1050°C, 1000°C, 1150°C or 1200°C.

[0030] The present invention further prefers that the pre-firing temperature in step (2) is 900-1200°C, which is conducive to the formation of a single microwave ferrite without impurities. If the pre-firing temperature is too low, the phase is not single and other impurities exist, such as an oxide phase that has not been completely reacted. If the pre-firing temperature is too high, the formed grains are too large, which is not conducive to the maintenance of coercive force. If the temperature is too high, the grains will melt and recrystallize, and the performance of the obtained microwave ferrite material will deteriorate.

[0031] Preferably, the heating rate of the pre-calcination in step (2) is 4-6°C / min, for example, 4°C / min, 5°C / min or 6°C / min.

[0032] Preferably, the pre-burning time in step (2) is 3 to 6 hours, for example, it can be 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0033] Preferably, the pre-firing atmosphere in step (2) includes an air atmosphere.

[0034] Preferably, before the second ball milling in step (3), the pre-sintered material in step (2) is crushed and mixed with a sintering aid and a ball milling dispersant to obtain a mixed slurry.

[0035] Preferably, the sintering aid includes any one of copper oxide, bismuth trioxide, boron oxide or vanadium pentoxide, or a combination of at least two of them, wherein typical but non-limiting combinations include a combination of copper oxide and bismuth trioxide, a combination of bismuth trioxide and boron oxide, or a combination of bismuth trioxide and vanadium pentoxide, etc.

[0036] Preferably, based on 100% of the total mass of the raw materials, the amount of the sintering aid is 2-3wt%, for example, 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt% or 3wt%.

[0037] Preferably, the ball milling dispersant includes any one of polyethylene glycol, sodium lauryl sulfate, sodium stearate or chitosan, or a combination of at least two of them, wherein typical but non-limiting combinations include a combination of polyethylene glycol and sodium lauryl sulfate, a combination of sodium lauryl sulfate and sodium stearate, or a combination of polyethylene glycol and chitosan, etc.

[0038] Preferably, based on the total mass of the raw materials as 100%, the amount of the ball milling dispersant used is 1 to 3wt%, for example, it can be 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2.0wt%, 2.2wt%, 2.5wt%, 2.8wt% or 3wt%, etc.

[0039] Preferably, step (3) further includes adjusting the pH of the mixed slurry before the second ball milling.

[0040] Preferably, the pH is adjusted to a pH of 8 to 10, for example, 8, 8.5, 9, 9.5 or 10, etc. The present invention further adjusts the pH of the mixed slurry in step (2) to 8 to 10. Within the pH range of 8 to 10, the electrostatic repulsion and van der Waals attraction between the particles in the mixed slurry reach a balance, thereby inhibiting the aggregation of the particles, facilitating the dispersion of the particles, and thus facilitating the subsequent second ball milling process.

[0041] Preferably, the rotation speed of the second ball mill in step (3) is 700-1100 r / min, for example, it can be 700 r / min, 750 r / min, 800 r / min, 850 r / min, 900 r / min, 950 r / min, 1000 r / min or 1100 r / min, etc.

[0042] Preferably, the second ball milling time in step (3) is 4 to 8 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.

[0043] Preferably, the drying method in step (3) includes oven drying.

[0044] Preferably, the drying temperature in step (3) is 70-100°C, for example, 70°C, 80°C, 90°C or 100°C.

[0045] Preferably, the granulation method in step (4) includes grinding granulation.

[0046] Preferably, the grinding and granulation process also includes adding a binder.

[0047] Preferably, the adhesive comprises any one of polyvinyl alcohol, polyacrylate or waterborne polyurethane, or a combination of at least two thereof, wherein typical but non-limiting combinations include a combination of polyvinyl alcohol and polyacrylate, a combination of polyacrylate and waterborne polyurethane, or a combination of polyvinyl alcohol and waterborne polyurethane, etc.

[0048] Preferably, the mass fraction of the adhesive is 5-12wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt% or 12wt%.

[0049] Preferably, the mass ratio of the second ball abrasive to the binder is (8.5-9.5):(0.5-1.5), for example, it can be 8.5:0.5, 8.5:0.7, 8.5:1.0, 8.5:1.3, 8.5:1.5, 9.0:0.5, 9.0:1.0, 9.0:1.5, 9.5:0.5, 9.5:0.8, 9.5:1.0, 9.5:1.2 or 9.5:1.5, etc.

[0050] The present invention further preferably has a mass ratio of the second ball mill to the binder of (8.5-9.5):(0.5-1.5), which is beneficial to improving the uniformity of dispersion of the second ball mill in the subsequent sintered embryonic body; if the amount of binder added is small, the material body will be dispersed farther during the sintering process, which is not conducive to sintering by solid phase reaction, and the density after sintering is small; if the amount of binder added is high, the material body will also be unevenly dispersed.

[0051] Preferably, the particle size of the second ball abrasive after granulation is 0.5-2 μm, for example, 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm or 2 μm.

[0052] Preferably, the pressing pressure in step (4) is 5 to 10 MPa, for example, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa.

[0053] Preferably, after the pressing step (4), a microwave ferrite bulk material is obtained, and the density of the microwave ferrite bulk material is 4.7 to 5.1 g / cm 3, for example, it can be 4.7 g / cm 3 , 4.8g / cm 3 , 4.9g / cm 3 , 5.0g / cm 3 or 5.1 g / cm 3 wait.

[0054] Preferably, the sintering in step (4) includes: a first heating and then a first heat preservation; and a second heating and then a second heat preservation.

[0055] Preferably, the terminal temperature of the first heating is 350-450°C, for example, 350°C, 380°C, 400°C, 420°C or 450°C.

[0056] Preferably, the first heating rate is 2-3°C / min, for example, 2°C / min or 3°C / min.

[0057] Preferably, the first insulation time is 0.5 to 2 hours, for example, 0.5 hours, 1 hour, 1.5 hours or 2 hours.

[0058] Preferably, the end point temperature of the second heating is 1050-1200°C, for example, it may be 1050°C, 1070°C, 1100°C, 1120°C, 1150°C, 1170°C or 1200°C.

[0059] Preferably, the second heating rate is 4-6°C / min, for example, 4°C / min, 5°C / min or 6°C / min.

[0060] Preferably, the second insulation time is 3 to 6 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0061] The present invention further selects the sintering to be carried out in a gradient heating and heat preservation manner, which is beneficial to improving the magnetoelectric properties of the microwave ferrite material.

[0062] As a preferred technical solution of the preparation method described in the second aspect of the present invention, the preparation method comprises the following steps:

[0063] (1) mixing a barium source, an iron source, a copper source and a co-substituted metal source, and performing a first ball milling at 800 to 1200 r / min for 6 to 8 hours to obtain a first ball milling slurry;

[0064] The barium source, iron source, copper source and co-substituted metal source are barium carbonate, iron oxide, copper oxide and co-substituted metal oxide respectively; the molar ratio of the sum of the copper oxide and the co-substituted metal oxide to the barium carbonate is (0.5-2.0):1.05; the molar ratio of the sum of the copper oxide and the co-substituted metal oxide to the iron oxide is (0.5-2.0):(9.2-10.6);

[0065] (2) pre-calcining the first ball-milled slurry in step (1) at 800 to 1200° C. for 3 to 6 hours to obtain a pre-calcined material; the pre-calcining heating rate is 4 to 6° C. / min;

[0066] (3) crushing the pre-sintered material in step (2) and mixing it with a sintering aid and a ball milling dispersant to obtain a mixed slurry; then adjusting the pH of the mixed slurry to 8-10; and then subjecting the mixed slurry to a second ball milling at 700-1100 r / min for 4-8 hours, washing and drying to obtain a second ball milled material;

[0067] (4) The second ball mill material and the binder are mixed in a mass ratio of (8.5-9.5): (0.5-1.5) to grind and granulate, and then pressed at a pressure of 5-10 MPa to obtain a density of 4.7-5.1 g / cm 3 A microwave ferrite block material is prepared; and finally, the microwave ferrite block material is sintered, wherein the sintering comprises: first heating the temperature to 350-450°C at a heating rate of 2-3°C / min, and then keeping the temperature for 0.5-2h; then heating the temperature to 1050-1200°C at a heating rate of 4-6°C / min, and then keeping the temperature for 3-6h; and finally, the microwave ferrite material is obtained.

[0068] In a third aspect, the present invention provides an application of the microwave ferrite material described in the first aspect, and the microwave ferrite material can be used in the field of wave absorption or electromagnetic shielding.

[0069] The microwave ferrite material provided by the present invention has a wide range of applications, for example, it can be used in the field of wave absorption or electromagnetic shielding. It not only has a higher wave absorption frequency, but also has high environmental stability and can meet the application requirements of more special scenarios.

[0070] Compared with the prior art, the present invention has at least the following beneficial effects:

[0071] (1) The microwave ferrite material provided by the present invention is doped with a specific amount of transition metal elements of different valences to replace the ferrite BaFe 12 O 19The Fe position in the material is increased while ensuring charge balance; the magnetocrystalline anisotropy field of the resulting microwave ferrite material is reduced, and the coercive force and saturation magnetic induction intensity are effectively adjusted by adjusting the doping amount, and the natural resonance frequency is continuously adjustable in the X-band (8.5-14.6 GHz) to meet the development needs of microwave communication towards high frequencies.

[0072] (2) The preparation method of the microwave ferrite material provided by the present invention further controls the mass ratio of each raw material, the pre-sintering temperature, the ball milling parameters and the sintering process; further improves the electromagnetic properties of the obtained microwave ferrite material, and the preparation method does not require complex synthesis equipment and highly toxic chemical reagents, the preparation process is simple and the cost is low, and it can be used for large-scale industrial production.

[0073] (3) The microwave ferrite material provided by the present invention can be used in the field of wave absorption or electromagnetic shielding. It not only has a higher wave absorption frequency, but also has high environmental stability and can meet the application requirements of more special scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 The microwave ferrite material BaFe provided in Example 1 of the present invention 10.5 (HfCu) 0.75 O 19 Magnetic hysteresis loop diagram of

[0075] Figure 2 The microwave ferrite material BaFe provided in Example 1 of the present invention 10.5 (HfCu) 0.75 O 19 Magnetic permeability spectrum of

[0076] Figure 3 The microwave ferrite material BaFe provided in Example 1 of the present invention 10 (HfCu)O 19 Magnetic hysteresis loop diagram of

[0077] Figure 4 The microwave ferrite material BaFe provided in Example 1 of the present invention 10 (HfCu)O 19 Magnetic permeability spectrum of

[0078] Figure 5 The microwave ferrite material BaFe provided in Example 1 of the present invention 11.5 (HfCu) 0.25 O 19 Magnetic permeability spectrum of

[0079] Figure 6 The microwave ferrite material BaFe provided in Example 2 of the present invention11.5 (ZrCu) 0.25 O 19 Magnetic permeability spectrum of

[0080] Figure 7 The microwave ferrite material BaFe provided in Example 2 of the present invention 10.5 (ZrCu) 0.75 O 19 Magnetic permeability spectrum of

[0081] Figure 8 The microwave ferrite material BaFe provided in Example 2 of the present invention 10 (ZrCu)O 19 Magnetic permeability spectrum. DETAILED DESCRIPTION

[0082] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0083] 1. Implementation

[0084] Example 1 This example provides a microwave ferrite material, whose chemical formula is BaFe (12-2x) (HfCu) x O 19 , where x is 0.25, 0.35, 0.5, 0.75, 0.8 and 1.0 respectively.

[0085] This embodiment also provides a method for preparing the microwave ferrite material. 10.5 (HfCu) 0.75 O 19 (x is 0.75) as an example, the preparation method comprises the following steps:

[0086] (1) 2.362 g of BaCO3, 10.035 g of Fe2O3, 0.714 g of CuO and 1.890 g of HfO2 were mixed to obtain raw materials, the raw materials, anhydrous ethanol and ball milling beads were mixed in a mass ratio of 2:3:4, and the first ball milling was performed at 1000 r / min for 7 h to obtain a first ball milling slurry;

[0087] (2) The first ball mill material of step (1) is washed with anhydrous ethanol and dried at 80° C.; then the temperature is increased to 1100° C. at a rate of 5° C. / min and pre-calcined for 4 h to obtain a pre-calcined material;

[0088] (3) crushing the pre-sintered material of step (2), and mixing 0.375 g Bi2O3 and 0.3 g CuO sintering aid with 0.14 g sodium dodecyl sulfate and 0.3 g polyethylene glycol dispersant to obtain a mixed slurry; adjusting the pH of the mixed slurry to 9; performing a second ball milling on the mixed slurry at 1000 r / min for 6 h, washing the second ball mill material with anhydrous ethanol, and then performing a second drying at 80° C. to obtain a second ball mill material;

[0089] (4) The second ball mill material and polyvinyl alcohol were mixed at a mass ratio of 9:1 and ground into granules, and then pressed at a pressure of 8 MPa to obtain a density of 5.0 g / cm 3 The microwave ferrite block material is sintered, wherein the sintering comprises: first heating the temperature to 400°C at a heating rate of 3°C / min, and then keeping the temperature for 1 hour; then heating the temperature to 1100°C at a heating rate of 5°C / min, and then keeping the temperature for 4 hours; finally, the microwave ferrite material is obtained;

[0090] The preparation methods of microwave ferrite materials with other x values ​​are the same as those of BaFe 10.5 (HfCu) 0.75 O 19 The preparation method is the same.

[0091] like Figure 1 and Figure 2 As shown, Figure 1 The microwave ferrite material BaFe obtained in this embodiment 10.5 (HfCu) 0.75 O 19 From the hysteresis loop diagram, it can be seen that its coercive force is very low and the saturation magnetization is relatively high, which is 56.2emu / g, confirming that the microwave ferrite material obtained in this embodiment has a lower coercive force and a higher saturation magnetization. Figure 2 The microwave ferrite material BaFe obtained in this embodiment 10.5 (HfCu) 0.75 O 19 The magnetic permeability spectrum of the material confirms that its natural resonance frequency is at 11.5 GHz.

[0092] like Figures 3-4 As shown, Figure 3 The microwave ferrite material BaFe obtained in this embodiment 10 (HfCu)O 19 The hysteresis loop diagram of the ferrite can confirm that it has a lower coercive force and a higher saturation magnetization (36.4emu / g). Figure 4 BaFe is the microwave ferrite material obtained in this example.10 (HfCu)O 19 The magnetic permeability spectrum confirms that its natural resonance frequency is 8.5 GHz.

[0093] like Figure 5 As shown, it is the microwave ferrite material BaFe obtained in this embodiment. 11.5 (HfCu) 0.25 O 19 The magnetic permeability spectrum of the material confirms that its natural resonance frequency is at 14.5 GHz.

[0094] Example 2

[0095] This embodiment provides a microwave ferrite material, whose chemical formula is BaFe (12-2x) (ZrCu) x O 19 , where x is 0.25, 0.35, 0.5, 0.75, 0.8 and 1.0 respectively.

[0096] This embodiment also provides a method for preparing the microwave ferrite material. 10 (ZrCu)O 19 (x is 1.0) as an example, the preparation method comprises the following steps:

[0097] (1) 2.470 g BaCO3, 9.993 g Fe2O3, 0.996 g CuO and 1.542 g ZrO2 were mixed to obtain raw materials, the raw materials, anhydrous ethanol and ball milling beads were mixed in a mass ratio of 1.5:2.5:3.5, and the first ball milling was performed at 800 r / min for 8 h to obtain a first ball milling slurry;

[0098] (2) washing the first ball mill material in step (1) with anhydrous ethanol and performing a first drying at 70° C.; then heating the ball mill material to 900° C. at a rate of 4° C. / min and pre-calcining the ball mill material for 6 h to obtain a pre-calcined ball mill material;

[0099] (3) crushing the pre-sintered material of step (2), and mixing 0.365 g Bi2O3 and 0.25 g CuO sintering aid with 0.15 g sodium dodecyl sulfate and 0.4 g polyethylene glycol dispersant to obtain a mixed slurry; adjusting the pH of the mixed slurry to 8; performing a second ball milling on the mixed slurry at 700 r / min for 8 h, washing the second ball mill material with anhydrous ethanol, and then performing a second drying at 70° C. to obtain a second ball mill material;

[0100] (4) The second ball mill material and polyvinyl alcohol were mixed at a mass ratio of 8.5:1 and ground into granules, and then pressed at a pressure of 10 MPa to obtain a density of 5.1 g / cm 3The microwave ferrite block material is prepared; and finally, the microwave ferrite block material is sintered, wherein the sintering comprises: first heating the temperature to 450°C at a heating rate of 2°C / min, and then keeping the temperature for 1.5 hours; and then heating the temperature to 1050°C at a heating rate of 4°C / min, and then keeping the temperature for 6 hours; and finally, the microwave ferrite material is obtained;

[0101] The preparation methods of microwave ferrite materials with other x values ​​are the same as those of BaFe 10 (ZrCu)O 19 The preparation method is the same.

[0102] like Figures 6 to 8 As shown, they are the microwave ferrite materials BaFe 11.5 (ZrCu) 0.25 O 19 ,BaFe 10.5 (ZrCu) 0.75 O 19 and BaFe 10 (ZrCu)O 19 From the magnetic permeability spectrum, it can be seen that the natural resonance frequencies are 14.3 GHz, 11 GHz and 10 GHz respectively.

[0103] Example 3

[0104] This embodiment provides a microwave ferrite material, whose chemical formula is BaFe (12-2x) (TiCu) x O 19 , where x is 0.25, 0.35, 0.5, 0.75, 0.8 and 1.0 respectively.

[0105] This embodiment also provides a method for preparing the microwave ferrite material. 11.5 (TiCu) 0.25 O 19 (x is 0.25) as an example, the preparation method comprises the following steps:

[0106] (1) 2.360 g of BaCO3, 10.012 g of Fe2O3, 0.710 g of CuO and 1.867 g of TiO2 were mixed to obtain raw materials, the raw materials, anhydrous ethanol and ball milling beads were mixed in a mass ratio of 2.5:3.5:4.5, and the first ball milling was performed at 1200 r / min for 6 h to obtain a first ball milling slurry;

[0107] (2) The first ball mill material of step (1) is washed with anhydrous ethanol and dried at 75° C.; then the temperature is increased to 1200° C. at a rate of 6° C. / min and pre-calcined for 3 h to obtain a pre-calcined material;

[0108] (3) crushing the pre-sintered material of step (2), and mixing 0.360 g Bi2O3 and 0.35 g CuO sintering aid with 0.15 g sodium dodecyl sulfate and 0.2 g polyethylene glycol dispersant to obtain a mixed slurry; adjusting the pH of the mixed slurry to 10; performing a second ball milling on the mixed slurry at 1100 r / min for 4 h, washing the second ball mill material with anhydrous ethanol, and then performing a second drying at 100° C. to obtain a second ball mill material;

[0109] (4) The second ball mill material and polyvinyl alcohol were mixed at a mass ratio of 9.5:1 and ground into granules, and then pressed at a pressure of 5 MPa to obtain a density of 4.7 g / cm 3 The microwave ferrite block material is sintered, wherein the sintering comprises: first heating the temperature to 350°C at a heating rate of 3°C / min, and then keeping the temperature for 2h; then heating the temperature to 1200°C at a heating rate of 6°C / min, and then keeping the temperature for 3h; finally, the microwave ferrite material is obtained;

[0110] The preparation methods of microwave ferrite materials with other x values ​​are the same as those of BaFe 11.5 (TiCu) 0.25 O 19 The preparation method is the same.

[0111] The microwave ferrite material obtained in this embodiment can also achieve adjustable natural resonance frequency within the X-band range, and under the same doping amount, that is, x value, the degree of reduction of the natural resonance frequency is equivalent to that of Example 1 or Example 2.

[0112] The natural resonance frequencies of the microwave ferrite materials prepared in Examples 1 to 3 were tested, and the results are shown in Table 1.

[0113] Table 1

[0114]

[0115] From Table 1 we can see that:

[0116] The present invention achieves continuous adjustment of the natural resonance frequency of the obtained microwave ferrite material within the X-band (8.5-14.6 GHz) by regulating the doping amount of Cu and the co-substituted metal element in the ferrite material to meet the use requirements in different bands; and it can be seen that as x increases, the degree of reduction of the natural resonance frequency is greater.

[0117] 2. Comparison

[0118] Comparative Example 1

[0119] This comparative example provides a microwave ferrite material, the chemical formula of which is BaFe 11.52 (HfCu) 0.24 O 19 The raw material quality in the preparation method is changed accordingly, and the rest is the same as the microwave ferrite material BaFe provided in Example 1. 10.5 (HfCu) 0.75 O 19 The preparation method is the same.

[0120] Since the microwave ferrite material BaFe 11.52 (HfCu) 0.24 O 19 The doping amounts of Hf and Cu are relatively small, resulting in still large magnetocrystalline anisotropy; this results in a high natural resonance frequency (31.2 GHz), which cannot be reduced to within the X-band and cannot meet the use requirements of the X-band.

[0121] Comparative Example 2

[0122] This comparative example provides a microwave ferrite material, the chemical formula of which is BaFe 9.6 (HfCu) 1.2 O 19 The raw material quality in the preparation method is changed accordingly, and the rest is the same as the microwave ferrite material BaFe provided in Example 1. 10.5 (HfCu) 0.75 O 19 The preparation method is the same.

[0123] The microwave ferrite material BaFe 9.6 (HfCu) 1.2 O 19 The natural resonance frequency is reduced to 2.1 GHz, but it still cannot meet the requirements of the X-band. In addition, due to the large doping amount of Hf and Cu, they cannot be completely incorporated into the lattice, and the presence of oxide impurities leads to poor performance.

[0124] Comparative Example 3

[0125] This comparative example provides a microwave ferrite material, the chemical formula of which is BaFe 11.25 Hf 0.75 O 19 The raw materials and their quality in the preparation method are changed accordingly, and the rest are the same as the microwave ferrite material BaFe provided in Example 1. 10.5 (HfCu) 0.75 O 19 The preparation method is the same.

[0126] The microwave ferrite material BaFe11.25 Hf 0.75 O 19 The natural resonance frequency is still relatively high, at 24.6 GHz, which cannot meet the requirements of X-band use. In addition, it is only doped with Hf, which causes the charge to be unbalanced, thus affecting the dielectric properties of the material.

[0127] Comparative Example 4

[0128] This comparative example provides a microwave ferrite material, the chemical formula of which is BaFe 10.5 (LaCu) 0.75 O 19 The raw materials and their quality in the preparation method are changed accordingly, and the rest are the same as the microwave ferrite material BaFe provided in Example 1. 10.5 (HfCu) 0.75 O 19 The preparation method is the same.

[0129] Since the microwave ferrite material BaFe 10.5 (LaCu) 0.75 O 19 Replacing the co-substituted metal with La results in an increase in magnetocrystalline anisotropy, which fails to reduce the natural resonance frequency. The natural resonance frequency is 21.3 GHz, which cannot meet the requirements of X-band use.

[0130] In summary, the microwave ferrite material of the present invention achieves continuous adjustment of the natural resonance frequency in the range of 8.5 to 14.6 GHz by doping a specific transition metal element (hafnium, zirconium or titanium) with a specific content (0.25≤x≤1.0) to replace the Fe position, while ensuring better dielectric properties.

[0131] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A microwave ferrite material, characterized in that: The chemical formula of the microwave ferrite material is BaFe (12-2x) (MeCu) x O 19 , wherein Me is a co-substituted metal, Me includes any one or a combination of at least two of hafnium, zirconium or titanium, and 0.25≤x≤1.

0.

2. The microwave ferrite material according to claim 1, characterized in that: The natural resonance frequency of the microwave ferrite material is continuously adjustable within the range of 8.5 to 14.6 GHz.

3. A method for preparing the microwave ferrite material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing a barium source, an iron source, a copper source and a co-substituted metal source and performing a first ball milling to obtain a first ball milling slurry; (2) pre-calcining the first ball-milled slurry in step (1) to obtain a pre-calcined material; (3) subjecting the pre-sintered material in step (2) to a second ball milling, washing and drying in sequence to obtain a second ball milled material; (4) The second ball mill material in step (3) is granulated, pressed and sintered in sequence to obtain the microwave ferrite material.

4. The preparation method according to claim 3, characterized in that: The barium source, iron source, copper source and co-substituted metal source in step (1) are barium carbonate, iron oxide, copper oxide and co-substituted metal oxide respectively; Preferably, the molar ratio of the sum of the copper oxide and the co-substituted metal oxide to the barium carbonate (0.5-2.0) is: 1.05; Preferably, the molar ratio of the sum of the copper oxide and the co-substituted metal oxide to the iron oxide is (0.5-2.0):(9.2-10.6); Preferably, the rotation speed of the first ball mill in step (1) is 800 to 1200 r / min; Preferably, the first ball milling time in step (1) is 6 to 8 hours.

5. The preparation method according to claim 3 or 4, characterized in that: The pre-burning temperature in step (2) is 900-1200° C. Preferably, the heating rate of the pre-burning in step (2) is 4 to 6°C / min; Preferably, the pre-burning time in step (2) is 3 to 6 hours.

6. The preparation method according to any one of claims 3 to 5, characterized in that: Step (3) before the second ball milling, the pre-sintered material of step (2) is crushed and mixed with a sintering aid and a ball milling dispersant to obtain a mixed slurry; Preferably, the sintering aid comprises any one of copper oxide, bismuth trioxide, boron oxide or vanadium pentoxide, or a combination of at least two thereof; Preferably, the ball milling dispersant includes any one or a combination of at least two of polyethylene glycol, sodium lauryl sulfate, sodium stearate or chitosan; Preferably, step (3) further comprises adjusting the pH of the mixed slurry before the second ball milling; Preferably, the pH is adjusted to a pH of 8 to 10 in the mixed slurry; Preferably, the rotation speed of the second ball mill in step (3) is 700-1100 r / min; Preferably, the second ball milling time in step (3) is 4 to 8 hours; Preferably, the particle size of the second ball mill is 0.5-2 μm.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The granulation method in step (4) includes grinding granulation; Preferably, the grinding and granulation process further comprises adding a binder; Preferably, the adhesive comprises any one or a combination of at least two of polyvinyl alcohol, polyacrylate or waterborne polyurethane; Preferably, the mass ratio of the second ball grinding material to the binder is (8.5-9.5):(0.5-1.5); Preferably, the pressure of the molding in step (4) is 5 to 10 MPa; Preferably, after the pressing in step (4), a microwave ferrite bulk material is obtained, and the density of the microwave ferrite bulk material is 4.7 to 5.1 g / cm 3 .

8. The preparation method according to any one of claims 3 to 7, characterized in that: The sintering in step (4) includes: first heating up and then heat preservation; then heating up and then heat preservation; Preferably, the end temperature of the first heating is 350-450°C; Preferably, the first heating rate is 2-3°C / min; Preferably, the first insulation time is 0.5 to 2 hours; Preferably, the end temperature of the second heating is 1050-1200°C; Preferably, the second heating rate is 4-6°C / min; Preferably, the second insulation time is 3 to 6 hours.

9. The preparation method according to any one of claims 3 to 8, characterized in that: The preparation method comprises the following steps: (1) mixing a barium source, an iron source, a copper source and a co-substituted metal source, and performing a first ball milling at 800 to 1200 r / min for 6 to 8 hours to obtain a first ball milling slurry; The barium source, iron source, copper source and co-substituted metal source are barium carbonate, iron oxide, copper oxide and co-substituted metal oxide respectively; the molar ratio of the sum of the copper oxide and the co-substituted metal oxide to the barium carbonate is (0.5-2.0):1.05; the molar ratio of the sum of the copper oxide and the co-substituted metal oxide to the iron oxide is (0.5-2.0):(9.2-10.6); (2) pre-calcining the first ball-milled slurry in step (1) at 800 to 1200° C. for 3 to 6 hours to obtain a pre-calcined material; the pre-calcining heating rate is 4 to 6° C. / min; (3) crushing the pre-sintered material in step (2) and mixing it with a sintering aid and a ball milling dispersant to obtain a mixed slurry; then adjusting the pH of the mixed slurry to 8-10; and then subjecting the mixed slurry to a second ball milling at 700-1100 r / min for 4-8 hours, washing and drying to obtain a second ball milled material; (4) The second ball mill material and the binder are mixed in a mass ratio of (8.5-9.5): (0.5-1.5) to grind and granulate, and then pressed at a pressure of 5-10 MPa to obtain a density of 4.7-5.1 g / cm 3 A microwave ferrite block material is prepared; and finally, the microwave ferrite block material is sintered, wherein the sintering comprises: first heating the temperature to 350-450°C at a heating rate of 2-3°C / min, and then keeping the temperature for 0.5-2h; then heating the temperature to 1050-1200°C at a heating rate of 4-6°C / min, and then keeping the temperature for 3-6h; and finally, the microwave ferrite material is obtained.

10. An application of the microwave ferrite material according to claim 1 or 2, characterized in that: The microwave ferrite material is used in the field of wave absorption or electromagnetic shielding.

Citation Information

Patent Citations

  • Magnetic material for antennas, antenna, and wireless communication device

    CN102682947A

  • Magnetoplumbite-type hexagonal ferrite

    CN104072117A

  • Resin composition

    JP2008169378A